Analisis Penentuan Kualitas Batubara Berdasarkan Uji Proksimat di PT. Pelabuhan Universal Sumatera Kabupaten Muaro Jambi, Provinsi Jambi - FEBRYANTI FEBRYANTI; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Universal Port of Sumatra is a company engaged in port services that handles loading and unloading of coal. Distribution of coal at PT. Universal Sumatra Port does not take place every day, but depends on consumer demand, therefore coal accumulation occurs in the long term. PT. Universal Sumatra Port has never tested the quality of coal. Meanwhile, in the Minister of Energy and Mineral Resources Decree Number 1827 of 2018 it is explained that, in stacking activities, efforts must be made to maintain the quality of stacked coal. One of the efforts to maintain the quality of coal is by conducting quality testing. Therefore, this study was conducted to determine the value of coal quality and rank (rank) of coal, as well as what factors can cause changes in the value of coal quality. To determine coal quality, proximate analysis was used with test parameters, namely, total moisture (TM), ash content (AC), volatile matter (VM), fixed carbon (FC), and calori value (CV). Based on the results of testing in the coal quality laboratory at PT. Universal Sumatra Port did not experience significant changes, namely the total moisture value of coal in stockpile 13.58 while on barge 15.21, ash content value in coal in stockpile 3.09 while on barge 3.27, volatile matter value in coal in stockpile 51.51 while on barge 51.11, and the calorific value of coal in stockpile is 5411.90 while on barge 5397.75. It can be assumed that coal at PT. Universal Sumatra Port is categorized at subbituminous rank B (based on coal classification according to ASTM).